Large eddy simulation of dynamic stall over an airfoil and its control with plasma actuator - Hengyang Zhang; Haocheng Yu; Ao Zhang; Jianguo Zheng (AIP Advances, 2023)
The purpose of this study is to investigate deep dynamic stall over a pitching National Advisory Committee for Aeronautics 0015 airfoil and its control with an alternating current dielectric barrier discharge (AC-DBD) plasma actuator by means of large eddy simulation. The airfoil oscillates at a reduced frequency of k = 0.08 with the angle of attack (AoA) varying between 5° and 25°. The chord-based Reynolds number is Re = 7.6 × 104. Rich fluid dynamics and physics involved in the dynamic stall are resolved by large eddy simulation. It is found that the dynamic stall under consideration initiates with the onset of a leading edge vortex (LEV). The deep dynamic stall is characterized and dominated by four successive LEVs at high angles of attack. The control of dynamic stall with AC-DBD plasma actuation is investigated in depth. At low AoAs, the plasma forcing can delay the laminar-to-turbulent transition of the attached flow over the suction surface of the airfoil. Although the formation of the first LEV is delayed by the plasma actuation, the first three LEVs cannot be effectively suppressed in high AoAs beyond 20°. The impact of the AC-DBD on the flow becomes increasingly pronounced in the downstroke phase, and at the intermediate angles of attack, the flow separation can be effectively controlled. Substantial gain from the flow control is obtained. The area of the lift hysteresis loop and drag force are appreciably reduced, and the nose-down pitch moment is alleviated notably. Finally, the influence of forcing frequency on flow control is examined.